ANALISIS KUALITAS BUTIR SOAL PILIHAN GANDA MATA PELAJARAN AGAMA DAN BUDI PEKERTI KELAS III SD ADVENT NABIRE MENGGUNAKAN ITEMEN - Purba, Efa Nurlinda; Hermenius Sujati (Jurnal Merah Putih Sekolah Dasar, 2025)
The purpose of this study was to analyze the quality of 20 multiple-choice questions in the second semester exam for the Religion and Ethics subject for third-grade students at SD Advent Nabire using the ITEMEN program. The analysis focused on the level of difficulty, discriminating power, and effectiveness of distractors. The results show that 65% of the questions are categorized as moderate and 35% as easy, with no difficult questions, indicating a lack of variety in challenges. The majority of questions (65%) have low to very low discriminating power, indicating their inability to distinguish students based on their level of understanding. However, 85% of the distractors function effectively, indicating a good distractor design. It was concluded that, although the distractors were good, the overall quality of the questions needed significant improvement in terms of discriminating power and difficulty level distribution in order to make the evaluation instrument more valid. Recommendations included revising problematic questions, increasing teachers' capacity in question writing, and developing a high-quality question bank.